2021
DOI: 10.14309/ajg.0000000000001153
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Famotidine in Hospitalized COVID-19 Patients

Abstract: INTRODUCTION: Famotidine has been posited as a potential treatment for coronavirus disease 2019 (COVID-19). We compared the incidence of COVID-19 outcomes (i.e., death and death or intensive services use) among hospitalized famotidine users vs proton pump inhibitors (PPIs) users, hydroxychloroquine users, or famotidine nonusers separately. METHODS: We constructed a retrospective cohort study using data from COVID-19 Premier Hospital electronic health re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
1
32
0
2
Order By: Relevance
“…Our study and other retrospective studies of famotidine suggest there may be an association between the use of famotidine and improved outcomes among hospitalized patients with COVID-19 4,5 ; this was also suggested by a case series of famotidine with quantitative symptom tracking in nonhospitalized patients. 3 The data from Yeramaneni et al and other retrospective studies 6,7 show no association. We agree with Yeramaneni et al that famotidine should only be used as COVID-19 therapy in the context of a clinical trial.…”
Section: (Covid-19)mentioning
confidence: 90%
“…Our study and other retrospective studies of famotidine suggest there may be an association between the use of famotidine and improved outcomes among hospitalized patients with COVID-19 4,5 ; this was also suggested by a case series of famotidine with quantitative symptom tracking in nonhospitalized patients. 3 The data from Yeramaneni et al and other retrospective studies 6,7 show no association. We agree with Yeramaneni et al that famotidine should only be used as COVID-19 therapy in the context of a clinical trial.…”
Section: (Covid-19)mentioning
confidence: 90%
“…In the study by Yeramaneni et al, 3 the severe course of illness was defined as death within 30 days of hospitalization. In the study by Shoaibi et al, 4 the severe course of illness was defined as combined death and/or the requirement for mechanical ventilation, tracheostomy, or extracorporeal membrane oxygenation. In the study by Mather et al, 5 the severe course of illness was defined as a composite of death or requirement for ventilation.…”
Section: Supplemental Online Materialsmentioning
confidence: 99%
“…Study characteristics are depicted in the Table. [3][4][5][6][7] All studies were retrospective and are deemed good quality with a Newcastle-Ottawa Scale ranging from 7 to 8 (Table ). The meta-analysis of 3 studies 4,5,7 (n¼31,563), which provided adjusted hazard ratio (aHR), revealed a nonsignificant association between the use of famotidine and the hazard for a severe course of illness in patients with COVID-19, relative to nonuse of famotidine (Figure; pooled HR¼0.83; 95% CI, 0.49 to 1.41).…”
mentioning
confidence: 99%
“…2. duplicate. The last 4 articles were included [2 5] . The HR values of Propensity Score Matching from 4 articles were extracted, the patient's serve disease or death or intubation data of famotidine and non-famotidine were converted into the corresponding log (RR) and SE (considering the low mortality of COVID19, it can be considered that the HR value is equivalent to the OR value) (Table 1 ).…”
mentioning
confidence: 99%
“…However, Mather et al believed that the matching of propensity scores to adjust for age differences between famotidine and non-famotidine patients did not change the significance of the differences in mortality or combined mortality and intubation in the analysis [4] . Similarly, Shoaibi et al stated that with real-world data from a large multi-agency hospital database, no evidence has been found that famotidine used in hospitalized COVID-19 patients reduced the risk of death compared with non-users [5] . To better understand these contradictions, we analyzed the data of these articles through meta-analysis.…”
mentioning
confidence: 99%